HPTLC Screening and Alpha-Glucosidase Inhibitory Activity of Ethanolic Extract of Marang (Artocarpus odoratissimus) Core Waste Fruit - Cabantac, Aileen (JPAIR Multidisciplinary Research, 2026)
Marang (Artocarpus odoratissimus) is a native Philippine tree commonly found in Southeast Asia, used to treat various ailments. To provide a scientific basis for such a claim, this study evaluated the potential of marang, focusing on the core waste fruit, as a natural treatment for diabetes that aligns with the Sustainable Development Goals and the circular economy by reducing resource waste and minimizing environmental impact. This study utilized a quantitative, descriptive, comparative, and experimental design to analyze data on the phytochemical constituents and alpha-glucosidase inhibitory activity. For the evaluation of glucosidase inhibition activity, in vitro methods, and statistical such as mean, standard deviation, One-Way ANOVA, Regression and Post Hoc were applied.  HPTLC screening revealed the presence of primary metabolites, including proteins, suggesting possible medicinal properties. Results showed a statistically significant difference (p
Keywords: Health Sciences; Artocarpus odoratissimus extract; alpha-glucosidase inhibition; phytochemical; antidiabetic activity; quantitative-experimental; Philippines